2016
DOI: 10.1002/ejic.201600687
|View full text |Cite
|
Sign up to set email alerts
|

Unique Colours of 3d‐Transition‐Metal‐Substituted Lyonsite Molybdates and Their Derivatives: The Role of Multiple Coordination Geometries and Metal‐to‐Metal Charge Transfer

Abstract: We describe the synthesis, crystal structures, and optical absorption spectra/colours of 3d transition‐metal‐substituted lyonsite‐type oxides Li3Al1–xMIIIx(MoO4)3 (0 < x ≤ 1.0; MIII = Cr, Fe) and Li3–xAl1–xMII2x(MoO4)3 (0 < x ≤ 1.0; MII = Co, Ni, Cu). The oxides were readily synthesized by the solid‐state reaction of stoichiometric mixtures of the constituent binaries at around 700 °C in air. The crystal structures determined by Rietveld refinement of PXRD data revealed that in the smaller trivalent‐metal‐subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Similar differences were also noted for the absorption edges/band gaps of the divalent wolframite tungstates AWO 4 (A = Mg, Mn, Co, Ni, Cu, Zn) and the lyonsite molybdates Li 3 Al(MoO 4 ) 3 and Li 2 Mg 2 (MoO 4 ) 3 as well as their transition‐metal (TM) analogues . The smaller charge‐transfer energies observed for TM wolframite tungstates and lyonsite molybdates compared with those of their non‐transition‐metal analogues were assigned to the MMCT transitions in which the partially occupied 3d orbitals of the TMs become the highest occupied molecular orbital (HOMO), and the empty 4d/5d states of molybdate/tungstate become the lowest unoccupied molecular orbital (LUMO).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Similar differences were also noted for the absorption edges/band gaps of the divalent wolframite tungstates AWO 4 (A = Mg, Mn, Co, Ni, Cu, Zn) and the lyonsite molybdates Li 3 Al(MoO 4 ) 3 and Li 2 Mg 2 (MoO 4 ) 3 as well as their transition‐metal (TM) analogues . The smaller charge‐transfer energies observed for TM wolframite tungstates and lyonsite molybdates compared with those of their non‐transition‐metal analogues were assigned to the MMCT transitions in which the partially occupied 3d orbitals of the TMs become the highest occupied molecular orbital (HOMO), and the empty 4d/5d states of molybdate/tungstate become the lowest unoccupied molecular orbital (LUMO).…”
Section: Resultssupporting
confidence: 66%
“…As part of the present study, we explored the possible substitution of the Te 6+ site in the Ni 3 TeO 6 structure by Mo 6+ ions. It has been suggested that the presence of empty 4d orbitals near the partially filled 3d orbitals would promote the transfer of 3d electrons into the empty 4d orbitals , . Our efforts towards the substitution of Mo 6+ ions in place of Te 6+ ions were partially successful, as we were limited to x = 0.25 in these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar differences were also observed for the absorption edges of the divalent wolframite tungstates AWO 4 (A = Mg, Mn, Co, Ni, Cu, Zn) [24] and the lyonsite molybdates Li 3 Al(MoO 4 ) 3 and Li 2 Mg 2 (MoO 4 ) 3 as well as their transition-metal (TM) analogues. [27] The smaller charge-transfer energies observed for TM wolframite tungstates and lyonsite molybdates compared with those of their non-transition-metal analogues were assigned to the metal-metal charge transfer (MMCT) transitions. In MMCT transitions, the partially occupied 3d orbitals of the TMs become the highest occupied molecular orbital (HOMO), and the empty 4d/5d states of molybdate/tungstate become the lowest unoccupied molecular orbital (LUMO).…”
Section: Bimg 1-x M X Vo 5 (M = Co Ni and Cu)mentioning
confidence: 99%
“…[a] Δ is the polyhedral distortion parameter defined by Δ= 1/N ∑ [{(r i −r)/r} 2 ]10 3 ; where N is the number of bonds and r i and r are individual and average bond lengths, respectively [12,32] …”
Section: Resultsmentioning
confidence: 99%